Trends and adverse pregnancy outcomes associated with preeclampsia: a multi-centre cross-sectional study in Hebei, China - Runfang Wang; LiYan Du; Jiaoyang Di; Ya Duan; Wenning Lian; Li Liu; Suxin Liu; Dandan Yang; Yan Huo (BMC Pregnancy and Childbirth)
Abstract Objective This study aimed to assess the incidence, trends, and adverse pregnancy outcomes associated with preeclampsia (PE), while further investigating whether these adverse outcomes differ by parity and the type of pregnancy—twin or singleton. Materials and methods A multicenter cross-sectional study was conducted in Hebei, China, spanning the years 2013 to 2022, enrolling a total of 455,456 women. The incidence rates and trends of PE and its subtypes were analyzed utilizing joinpoint regression analysis, while modified Poisson regression was employed to assess the association between PE and adverse pregnancy outcomes. Effect modification by parity, twin or singleton pregnancy was also evaluated. Results The prevalence of PE and its stratification by singleton pregnancies and parity (primiparas versus multiparas) exhibited upward trends, with no statistically significant changes observed in the incidence of twins affected by PE from 2013 to 2022 in Hebei Province. After adjusting for sociodemographic characteristics and other comorbidities during pregnancy, patients with PE experienced significantly elevated risks of cesarean section (adjusted relative risk [aRR], 4.78; 95% confidence interval [CI], 4.54–5.02), postpartum hemorrhage (aRR, 1.97; 95% CI, 1.75–2.21), placental abruption (aRR, 1.52; 95% CI, 1.37–1.69), preterm birth (aRR, 5.35; 95% CI, 5.14–5.56), small for gestational age (SGA) newborns (aRR, 2.48; 95%CI, 2.38–2.58), maternal near-miss events (MNM) (aRR, 1.18; 95% CI, 1.01–1.38), and admission to the neonatal intensive care unit (NICU) (aRR, 1.27; 95% CI, 1.11–1.44). In contrast, the risk of placenta previa was significantly lower (aRR, 0.26; 95% CI, 0.21–0.32). The risks of cesarean section, postpartum hemorrhage, and preterm birth ascribable to PE were conspicuously augmented in twin pregnancies; conversely, the risk of placental abruption was more notable in singletons. The influence on cesarean delivery was pronounced in primiparas, while the risks of MNM, placental abruption, and preterm birth related to PE escalated in multiparas. Conclusions The incidences of PE in overall, singletons, primiparas and multiparas exhibited upward trends in Hebei from 2013 to 2022. Women afflicted with PE demonstrated a conspicuously augmented risk of adverse pregnancy outcomes and the magnitude of the influence of PE varied with singleton or twin pregnancies and parity.